The Medici effect : what elephants and epidemics can teach us about innovation : with a new preface and discussion guide - Johansson, Frans, ....- (Boston (Mass.) : Harvard Business Review Press, 2017)
Why do so many world-changing insights come from people with little or no related experience? Charles Darwin was a geologist when he proposed the theory of evolution. And it was an astronomer who finally explained what happened to the dinosaurs. Frans Johansson's The Medici Effect shows how breakthrough ideas most often occur when we bring concepts from one field into a new, unfamiliar territory, and offers examples how we can turn the ideas we discover into path-breaking innovations. Clayton M. Christensen--bestselling author of The Innovator's Dilemma--has described The Medici Effect as "one of the most insightful books about managing innovation I have ever read. Its assertion that breakthrough principles of creativity occur at novel intersections is an enduring principle of creativity that should guide innovators in every field." Now with a new preface and a reading guide, The Medici Effect is timeless classic that will help you reach your innovative peak.--
Part 1. The intersection: Chapter 1. The intersection: your best chance to innovate: monkeys and mind readers -- Chapter 2: The rise of intersections: the sounds of Shakira and the emotions of Shrek -- Part 2. Creating the Medici effect: Chapter 3: Break down the barriers between fields: sea urchin lollipops and Darwin's finches -- Chapter 4: How to make the barriers fall: Heathrow tunnel and restaurants without food -- Chapter 5: Randomly combine concepts: card games and sky rises -- Chapter 6: How to find the combinations: meteorite crashes and code breakers -- Chapter 7: Ignite an explosion of ideas: submarines and tubular bells -- Chapter 8: How to capture the explosion: MacGyver and boiling potatoes -- Part 3. Making intersectional ideas happen: Chapter 9: Execute past your failures: violence and school curricula -- Chapter 10: How to succeed in the face of failure: palm pilots and counterproductive carrots -- Chapter 11: Break out of your network: ants and truck drivers -- Chapter 12: How to leave the network behind: penguins and meditation -- Chapter 13: Take risks and overcome fear: airplanes and serial entrepreneurs -- Chapter 14: How to adopt a balanced view of risk: elephants and epidemics -- Chapter 15: Step into the intersection...and create the Medici effect.
Originally published as: The Medici effect : breakthrough insights at the intersection of ideas, concepts, and cultures
Includes bibliographical references and index.
Keywords: Creative thinking; Technological innovations